2018
DOI: 10.1093/pcp/pcy044
|View full text |Cite
|
Sign up to set email alerts
|

The Use of RNA Sequencing and Correlation Network Analysis to Study Potential Regulators of Crabapple Leaf Color Transformation

Abstract: Anthocyanins are plant pigments that contribute to the color of leaves, flowers and fruits, and that are beneficial to human health in the form of dietary antioxidants. The study of a transformable crabapple cultivar, 'India magic', which has red buds and green mature leaves, using mRNA profiling of four leaf developmental stages, allowed us to characterize molecular mechanisms regulating red color formation in early leaf development and the subsequent rapid down-regulation of anthocyanin biosynthesis. This an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 87 publications
1
20
0
Order By: Relevance
“…An analysis of the relationship between modules and anthocyanin levels revealed that the 'MEpink' module (r = 0.86, P = 1e-04) and the 'MEblue' module (r = 0.89, P = 9e-04) highly correlated with anthocyanin accumulation. Many DEGs identified in the MEpink and MEblue modules were TFs, including members of the MYB (MD17G1261100, MD09G 1278600, MD05G1120600), bHLH (MD14G1182700), SPL (MD12G1060200, MD13G1120300), WRKY (MD08G1094900, MD15G1078200, MD17G1223100), and ERF (MD15 G1221100, MD02G1096500) families (Table S10), which are all known to play important roles in anthocyanin biosynthesis (Lepiniec et al, 2006;Klee and Giovannoni, 2011;Jaakola, 2013;Pesch et al, 2015;Yang et al, 2018b).…”
Section: Construction Of a Co-expression Network With A Focus On Anthmentioning
confidence: 99%
“…An analysis of the relationship between modules and anthocyanin levels revealed that the 'MEpink' module (r = 0.86, P = 1e-04) and the 'MEblue' module (r = 0.89, P = 9e-04) highly correlated with anthocyanin accumulation. Many DEGs identified in the MEpink and MEblue modules were TFs, including members of the MYB (MD17G1261100, MD09G 1278600, MD05G1120600), bHLH (MD14G1182700), SPL (MD12G1060200, MD13G1120300), WRKY (MD08G1094900, MD15G1078200, MD17G1223100), and ERF (MD15 G1221100, MD02G1096500) families (Table S10), which are all known to play important roles in anthocyanin biosynthesis (Lepiniec et al, 2006;Klee and Giovannoni, 2011;Jaakola, 2013;Pesch et al, 2015;Yang et al, 2018b).…”
Section: Construction Of a Co-expression Network With A Focus On Anthmentioning
confidence: 99%
“…The statistical enrichment of the DEGs in KEGG pathways was tested by KOBAS 43 . The R package WGCNA was used to identify modules of highly correlated genes based on the FPKM data 44,45 . We filtered the genes based on gene expression and variations by using the R package DCGL.…”
Section: Kegg Enrichment Analysis Of Degs and Identification Of Coexpmentioning
confidence: 99%
“…The top 100 hub genes were calculated by eigengenebased connectivity, ranked by k (k cor,i (q) = cor(xi, E(q) ) and ME (module eigengene). KOBAS 2.0 was used for gene annotation 44 .…”
Section: Visualization Of Hub Genesmentioning
confidence: 99%
See 1 more Smart Citation
“…RNA concentration was measured using a Qubit ® RNA Assay Kit in a Qubit ® 2.0 fluorometer (Life Technologies, CA, USA). RNA integrity was assessed using an RNA Nano 6000 Assay Kit and a Bioanalyzer 2100 system (Agilent Technologies, CA, USA) (Yang et al, 2018).…”
Section: Rna Quantification and Quality Analysismentioning
confidence: 99%